(3QSGdI aj JMbjb GdcdjGJs - (3GdbWH GdJMJGfj , eMeO (B( (3eMehO (B) (3Hf eMeO GdQGRj, CHh YHO Gddg, bWH GdOjf CHh YHO Gddg GdJMJGfj,J (B766 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNJQY eGgjGJ GdGTjGA hHYO agPg QSGdI ai JMbjb GdcdjGJ eQJHI Ydi bhGYO hNGJeI s
(3BNQgG (B:s
(3adfcJa HgPG GdbOQ ai gPG GdebGe aGefgG ef GdeJadSajf hGdLGgdjf hGfYe HgG Ydi GdeSJYOjf hGdaGVdjf s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B38 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: 763s
Keywords: (3GdadSaI hGdefWbs